2003
DOI: 10.1111/1475-682x.00043
|View full text |Cite
|
Sign up to set email alerts
|

Juggling Models of Masculinity: Russian‐Jewish Immigrants in the Israeli Army

Abstract: The present study addresses the question "What is masculinity?" by exploring how male immigrants interpret local masculinity and the models of masculinity they portray while situating themselves in the male hierarchy of the new society. The study is based on "immigration stories" elicited by in-depth interviews conducted with 43 university students who immigrated to Israel at the beginning of the 1990s from the former Soviet Union. The analysis of the stories reveals that the immigrants employ four major pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 12 publications
(8 reference statements)
0
26
0
Order By: Relevance
“…These observations show that the South African military likewise has its own multiple definitions of masculinities with dynamic hierarchies of identity. This vindicates the view that in every society internationally and nationally the hegemonic model of masculinity categorises groups of men in relation to each other through normalising the definitions of masculinity and defining its standards and proper manifestations (Connell, 1995;Agostino, 2003;Lomsky-Feder & Rapoport, 2003).…”
Section: Contends That Hiv Infections Are Concentrated In the Lower Rmentioning
confidence: 92%
“…These observations show that the South African military likewise has its own multiple definitions of masculinities with dynamic hierarchies of identity. This vindicates the view that in every society internationally and nationally the hegemonic model of masculinity categorises groups of men in relation to each other through normalising the definitions of masculinity and defining its standards and proper manifestations (Connell, 1995;Agostino, 2003;Lomsky-Feder & Rapoport, 2003).…”
Section: Contends That Hiv Infections Are Concentrated In the Lower Rmentioning
confidence: 92%
“…The intensive socialization process that youths experience for social solidarity and responsibility leads them to adopt the image of defenders of the community (Lomsky-Feder & Rapoport, 2003). The context of routine versus emergency situations derived from warfare may be considered to be a salient characteristic of community life and to have the potential to affect motives for volunteering.…”
Section: Life Stages and Gender Differences In The Experience Of Volumentioning
confidence: 99%
“…Studies have shown that despite a certain diversity of hegemonic and counter-hegemonic masculinities, the army remains a stronghold of male and heterosexual domination, with far-reaching implications for gender relations in society generally (Ben-Ari and Lomsky-Feder, 1999;Izraeli, 1997;Lomsky-Feder and Rapoport, 2003;Sasson-Levy, 2003). For one thing, as a result of mandatory conscription, the entry of most Jewish male and female adolescents into civil society is mediated through an intensely patriarchal and warring institution (Golan, 1997).…”
Section: The Feminist Counter-discourse and The Attempt To Unmask Bitmentioning
confidence: 99%